Pulmonary oxygen uptake and muscle oxygenation responses to exercise in well-trained young and middle-aged cyclists - Dascombe, B. J. (Central Queensland University, 2007)
This thesis details four consecutive research investigations which were designed to examine the effect of age on the pulmonary oxygen uptake (VO2) and muscle oxygenation (mOxy) responses to exercise in well-trained cyclists